(untitled) (Mantichora. Italian Journal of Performance Studies, 2026)
The article aims to analyze, from the perspective of performance studies, the layered activity of writer Fulvio Abbate starting with hisinterest in the valorization of objects and commodities. In hisliterary production, in the decade-long YouTube channel “Teledurruti,” and finally in the monologue Il teatro degli oggetti, Abbate’s maniacal attention to objects-signs of various natures represents the key to reactivatin geach time ex novo the paradigmatic evocation of a generational and personal biography.